MANUAL ON STUDENTS' COUNSELLING FOR COLLEGE TEACHERS - ED. CHANDRASHEKAR. C. R.; Suresh, Kumar, Moily , Raghuram , Parthasarathy, Sekar, John (NATIONAL INST. OF MENTAL HEALTH & NEUROSCIENCES, BANGLORE, 2008)
To Address this issue, NIMHANS has worked out a programme to involve college teachers in counselling and act as referral and support giving agents for students with psychological problems. The manual with help teachers to caters to the needs of the college students through counselling.